Komponen-Komponen Other Comprehensive Income dan Relevansi Risiko Comprehensive Income - Adrian Syah; Herlina Helmy (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to examine the risk relevance net income, comprehensive income, and component-competent other comprehensive income. Specifically, this study investigates the risk relevance of net income volatility, comprehensive income volatility, and component-component other comprehensive income volatility on stock return volatility. The study population was finance and banking companies listed in Indonesia Stock Exchange period 2013-2017. Samples are selected with purposive sampling method. This study employed a quantitative method with simple linear regression because for variable tested had a number of different samples. The result of this research showed the risk relevance net income and comprehensive income can not be proven statistically. But of the five component of OCI only volatility change in the fair value of a financial instrument in a cash flow hedge are shown to have a significant positive effect on volatility stock return.